Credit Risk, Cost of Capital and Excessive Financial Leverage (2020)
Conventionally, business valuation methods do not usually incorporate explicitly the effects that the probable bankruptcy costs of the firm could have on the cost of capital. Doing this introduces a stress test in the estimation of the discount rate, which can be very relevant for the fair valuation of excessively leveraged companies traded on the stock market. In this sense, the purpose of this article is to demonstrate the resulting financial vulnerability for this type of firms by explicitly adjusting the cost of capital for bankruptcy risk, and highlighting its implications for the stock market and bank debt market, based on a comparative analysis between three alternative methods of calculating the weighted average cost of capital.